Research methods in intercultural communication : (Wiley-Blackwell, 2016)
Research Methods in Intercultural Communication introduces and contextualizes the most important methodological issues in the field for upper-level undergraduate and graduate students. Examples of these issues are which paradigms and how to research multilingually, interculturally and ethnically.